2017
DOI: 10.1136/bmjopen-2016-014120
|View full text |Cite
|
Sign up to set email alerts
|

Understanding repeated non-attendance in health services: a pilot analysis of administrative data and full study protocol for a national retrospective cohort

Abstract: IntroductionUnderstanding the causes of low engagement in healthcare is a pre-requisite for improving health services’ contribution to tackling health inequalities. Low engagement includes missing healthcare appointments. Serially (having a pattern of) missing general practice (GP) appointments may provide a risk marker for vulnerability and poorer health outcomes.Methods and analysisA proof of concept pilot using GP appointment data and a focus group with GPs informed the development of missed appointment cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 25 publications
1
94
0
6
Order By: Relevance
“…Medical imaging departments provide a vital role in patient care and can provide accurate diagnostic information, reducing the need for investigative surgery or other risky and more costly interventions . Poor attendance rates may have flow on effects in other departments and lead to poorer health and economic outcomes . Therefore, there is value in understanding the rates of non‐attendance in the medical imaging department context and investigating factors that are likely associated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical imaging departments provide a vital role in patient care and can provide accurate diagnostic information, reducing the need for investigative surgery or other risky and more costly interventions . Poor attendance rates may have flow on effects in other departments and lead to poorer health and economic outcomes . Therefore, there is value in understanding the rates of non‐attendance in the medical imaging department context and investigating factors that are likely associated.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Poor attendance rates may have flow on effects in other departments and lead to poorer health and economic outcomes. 7,8 Therefore, there is value in understanding the rates of nonattendance in the medical imaging department context and investigating factors that are likely associated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we undertook some preliminary research, which confirmed that a small core group of patients who miss multiple appointments did indeed exist. In addition, the odds of missing a subsequent appointment increase among patients who had missed at least one appointment in the previous 12 months (Waller & Hodgkin, 2000;Williamson et al, 2017). This was confirmed in later work (Figure 1), which already has significant implications for patients, practitioners, and service managers.…”
Section: Data Acquisitionmentioning
confidence: 65%
“…The study was conducted in 15 megacities with the highest physician-population ratios in the United States, and concluded that despite the large number of physicians in each megacity, a large number of patients had to wait 14 days or more to see their physician [20][21]. Williamson et al have also stated that one of the main reasons for not visiting a specialist wasthe large distance between medical centers and patients' place of residence [29].…”
Section: Discussionmentioning
confidence: 99%